Narrative inquiry into language teacher identity : ALTs in the JET program - Hiratsuka, Takaaki (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book provides insights for both native language teachers and local language teachers alike who conduct team-taught lessons by revisiting the topic of foreign assistant language teachers (ALTs), the Japan Exchange and Teaching (JET) program, and team teaching. This book is innovative in that (a) it is the first to elucidate ALTs' experiences comprehensively, across both historical time (i.e., prior to, during, and after the JET program) and social space (i.e., inside and outside the school), thereby revealing their multiple identities that they come to construct and reconstruct over time and (b) it explores the meanings and perspectives of particular phenomena that ALTs experience within their specific social settings from their own individual points of view. This inquiry does this by using personal narrative accounts gathered from multiple participants. Through these narrative accounts, Hiratsuka formulates a conceptualization of ALT identity, an effort that has hitherto been neglected. As a consequence, this book offers several practical and empirical applications of the conceptualization to future endeavors involving native language teachers and those who engage with them, including the key stakeholders of local language teachers, their local boards of education, the governments, and language learners across the globe"--
1. Introduction 2. ALTs and the JET program 3. ALT identity 4. The inquiry 5. Narratives of the participants 6. Foreigner identity 7. Dabbler identity 8. Internal factors 9. External factors 10. Conclusion
Keywords: JET Puroguramu; Language and languages -- Study and teaching -- Japan; Teaching teams -- Japan; Teachers' assistants -- Japan; Teachers, Foreign -- Japan; Educational exchanges -- Japan; LANGUAGE ARTS & DISCIPLINES / Study & Teaching